2014
DOI: 10.1007/978-1-4939-1782-2_9
|View full text |Cite
|
Sign up to set email alerts
|

The Olivo-Cerebellar System as a Neural Clock

Abstract: The cerebellum, and the olivo-cerebellar system in particular, may be the central mechanism of a neural clock that provides a rhythmic neural signal used to time motor and cognitive processes. Several independent lines of evidence support this hypothesis. First, the resting membrane potential of neurons in the inferior olive oscillates at ~10 Hz and the neural input from the olive leads to rhythmic complex spikes in cerebellum Purkinje cells. Second, the repeating modular microstructure of the cerebellum is id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…The finding supports models of sensory-motor timing in humans that propose that the IO provides information for monitoring absolute time (Teki et al, 2012;Ashe and Bushara, 2014). Those models are based on the findings of strong IO activation triggered by deviations in the expected timing of sensory events (Teki et al, 2011;Wu et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The finding supports models of sensory-motor timing in humans that propose that the IO provides information for monitoring absolute time (Teki et al, 2012;Ashe and Bushara, 2014). Those models are based on the findings of strong IO activation triggered by deviations in the expected timing of sensory events (Teki et al, 2011;Wu et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…One alternative possibility is that more precise temporal information is encoded by phase differences between populations of oscillatory IO neurons (Welsh et al, 1995; Welsh and Llinás, 1997;Jacobson et al, 2008). In this case, temporal codes in the primate cerebellar cortex would only be evident using large-scale recording of the CF responses of thousands of PCs using methods that have been implemented at small scale in rodents (Welsh et al, 1995;Ozden et al, 2009, De Gruijl et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in case of a varying external force input the adapting system has to anticipate the prospective change. Some research indicates that in particular a circuit between the cerebellum and the ION is involved in this forward controlling process [32,38,40,41,50,51]. This circuitry seems to be of special relevance for the characteristics of force profile applied by the tester during the MMT and will be discussed.…”
Section: Introductionmentioning
confidence: 94%
“…PCs receive a massive convergence of inputs from parallel fibres, a factor which allows an integration of neural information from distinct sources. The activities of complex spikes following discharges in the inferior olivary complex are viewed as a teaching signal (trial-and-error during a learning process) or a motor clock signal which provides a rhythmic neural signal used to time motor processes for time perception to production of timed movements [ 47 49 ]. Others have suggested that complex spikes exert a synchronization effect in the cerebellar cortex, both within and between the cerebellar microcomplexes [ 50 ].…”
Section: The Role Of the Cerebellum In Motion Controlmentioning
confidence: 99%